The Improvement of first Iteration Log Periodic Fractal Koch Antenna with Slot Implementation - N. S. M. Yaziz; M. K. A. Rahim; F. Zubir; N. S. Nadzir; R. Dewan; H. A. Majid (Institute of Advanced Engineering and Science, 2018)
In this paper, a slotted is introduced at each of the radiating elements on the 1st iteration log periodic fractal Koch antenna (LPFKA). The antenna is designed to testify the appropriate performance at UHF Digital television which operates from 4.0 GHz to 1.0 GHz. The dimension of the conventional 0th iteration LPKFA is successfully reduced by 17% with the implementation of slotted. The results show a good agreement with a stable radiation pattern across the operating bandwidth, stable gain more than 5 dBi and reflection coefficient of below -10 dB over the desired frequency range.